Compliance with 2023 WSCUC Standards Worksheet (2023)
This worksheet serves two purposes: 1. To provide reviewers ready access to evidence that demonstrates the institution is in compliance with Commission Standards 2. To prompt conversation within the institution regarding institutional capacity and infrastructure, strengths, weaknesses, priorities, and plans for ensuring compliance with the Standards